High performance elastomers & polymers for oil & gas 2010 : Aberdeen, 27-28 April 2010 : [conference proceedings] - International Conference [on] High Performance Elastomers & Polymers for Oil & Gas (5th : 2010 : Aberdeen, Scotland) (Shrewsbury : Smithers Rapra Technology)
Includes bibliographical references